Recent advances in the influenza virus vaccine landscape: a comprehensive overview of technologies and trials - Clark,TW; Tregoning,JS; Lister,H; Poletti,T; Amin,F; Nguyen-Van-Tam,JS (Clinical Microbiology Reviews, 2024)
In the United Kingdom (UK) in 2022/23, influenza virus infections returned to the levels recorded before the COVID-19 pandemic, exerting a substantial burden on an already stretched National Health Service (NHS) through increased primary and emergency care visits and subsequent hospitalizations. Population groups ≤4 years and ≥65 years of age, and those with underlying health conditions, are at the greatest risk of influenza-related hospitalization. Recent advances in influenza virus vaccine technologies may help to mitigate this burden. This review aims to summarize advances in the influenza virus vaccine landscape by describing the different technologies that are currently in use in the UK and more widely. The review also describes vaccine technologies that are under development, including mRNA, and universal influenza virus vaccines which aim to provide broader or increased protection. This is an exciting and important era for influenza virus vaccinations, and advances are critical to protect against a disease that still exerts a substantial burden across all populations and disproportionately impacts the most vulnerable, despite it being over 80 years since the first influenza virus vaccines were deployed.